The Integration Of Quality Management System ISO 9001: 2008 And Malcolm Baldrige Criteria For Performance Excellence (MBCfPE) At PT Petrokimia Gresik - Wahyudi, Disty Amelinda; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This research aims to analyze the implementation of the quality management system ISO 9001: 2008, Malcolm Baldrige Criteria for Performance Excellence (MBCfPE) as well as integration between ISO and MBCfPE in PT Petrokimia Gresik. The qualitative descripitive approach is used to analyze the implementation of ISO and MBCfPE, and the integration of the two management systems. The object of this research is PT Petrokimia Gresik. The company is implementing both of the management systems to improve the performance of the company. This research was conducted by studying the documents and in depth interviews with the company staff. The results of this research showed that the application of the ISO in PT Petrokimia Gresik has been in accordance with the requirements of ISO 9001: 2008 to manage processes that produce products according to the needs and expectations of customers. The study also shows that PT Petrokimia Gresik has been able to manage the work systems and work processes in accordance with the requirements of the Baldrige criteria to improve the company's performance from time to time. The results of the research also showed that there is a relationship (integration) between ISO and Baldrige. The application of ISO proved to help the company in obtaining a high score on the implementation of the Baldrige especially Category 6: focus on operations. However, the integration of both management systems can not be proven through documents. Â Key words: Quality Management System ISO 9001:2008, MBCfPE, and Integration